2016
DOI: 10.1021/acssuschemeng.6b01098
|View full text |Cite
|
Sign up to set email alerts
|

Spent Coffee Bioelastomeric Composite Foams for the Removal of Pb2+ and Hg2+ from Water

Abstract: Herein we present an interesting approach for the reutilization of coffee waste in water remediation. This is achieved by the development of bioelastomeric foams composed of 60 wt % of spent coffee powder and 40 wt % of silicone elastomer using the sugar leaching technique. In this study, we present the necessary characteristics of the developed “green” foams for the successful removal of Pb2+ and Hg2+ ions from water, and we identify the involved mechanisms. The capability of the bioelastomeric foams to inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…The theoretical maximum adsorption capacity ( Q max theor ) values obtained by the Langmuir isotherm fitting are quite similar to the Q max experimental values (Table S3, Supporting Information) confirming the validity of the model. The dimensionless constant ( R L ) calculated from the parameters obtained with the Langmuir isotherm is an equilibrium parameter called separation factor, which can be used to define whether a process is favorable . For all the adsorbents, the R L values are 0 < R L < 1, confirming that the MB adsorption on the adsorbent materials is favorable (0.014, 0.009, and 0.144 for SFOP foam, SF foam, and OP powder, respectively).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The theoretical maximum adsorption capacity ( Q max theor ) values obtained by the Langmuir isotherm fitting are quite similar to the Q max experimental values (Table S3, Supporting Information) confirming the validity of the model. The dimensionless constant ( R L ) calculated from the parameters obtained with the Langmuir isotherm is an equilibrium parameter called separation factor, which can be used to define whether a process is favorable . For all the adsorbents, the R L values are 0 < R L < 1, confirming that the MB adsorption on the adsorbent materials is favorable (0.014, 0.009, and 0.144 for SFOP foam, SF foam, and OP powder, respectively).…”
Section: Resultsmentioning
confidence: 89%
“…Nevertheless, its wide use in large‐scale water treatment could be considerably difficult, due to the time‐consuming and complicated processes required for the recovery of the powder after the remediation process. A strategy to improve the handling of OP for water remediation applications may be the fixing of the powder in a solid porous system . The polluted water can permeate the porous solid, where aqueous pollutants can selectively interact and concentrate on the OP active component.…”
Section: Introductionmentioning
confidence: 99%
“…However, the reason that relatively low concentrations of arsenic were observed is due to the small surface area and volume of untreated coffee grounds. Therefore, pretreating the untreated coffee wastes such as calcination to eliminate the impurities and modification with other cation reagents would be necessary to improve the adsorption capacity of the coffee waste [30].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Azouaou et al demonstrated that the adsorption of cadmium was observed in aqueous solutions by using untreated coffee grounds [29]. In addition, lead and mercury from wastewater were removed using spent coffee bioelastomeric composite forms in a study by Fragouli et al [30]. However, to the best of our knowledge, no study to remove arsenic from the wastewater by using untreated coffee grounds has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of solids used for all experiments was 0.12 g and the volume of aqueous solution was 20 mL, with a metal concentration ranging between 20 and 100 ppm, as previously reported [27].…”
Section: Methodsmentioning
confidence: 99%